2019
DOI: 10.3390/jcm8070975
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Injection of Hydrolyzed Collagen to Treat Symptoms of Knee Osteoarthritis. A Functional In Vitro Investigation and a Pilot Retrospective Clinical Study

Abstract: Among all joints affected, knee osteoarthritis has a prevalence of about 10% in men and 13% in women over 60 years old. Knee osteoarthritis has high economic and social costs and may have a devastating impact on patient quality of life. Treatment of symptomatic knee Osteoarthritis may involve oral or topical administration of non-steroidal anti-inflammatory drugs or intra-articular injection of corticosteroids. Recently, a novel injectable collagen formulation (ChondroGrid) consisting of bovine hydrolyzed <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 37 publications
1
28
0
2
Order By: Relevance
“…Placebo Oral/2 capsules (1 g) of BCC, 2 times daily 1 capsule = 300 mg hydrolyzed collagen type II + 100 mg CS + 50 mg HA Chicken/∼1.5 − 2.5 kDa Stančík (2012) [ 68 ] Slovakia RCT (double-blind) Knee OA patients Undenatured type I collagen (COL-I) vs. Placebo Oral/1 × 8 mg pure lyophilized collagen type I in capsule Bovine/NA Trč (2011) [ 69 ] Czech Republic RCT (double-blind) Knee OA patients Enzymatic hydrolyzed collagen vs. glucosamine sulphate Oral/10 g, once daily NA/NA Observational studies Azeem (2019) [ 70 ] India Open-label observational study Knee OA patients UC-II (undenatured type II collagen)/no control Oral/daily capsule of 40 g of UC-II Obtained from chicken sternum/NA De Luca (2019) [ 71 ] Italy Retrospective study Knee OA patients An injectable collagen formulation consisting of bovine hydrolyzed type I collagen (ChondroGrid) / No control Intra-articular injection/ Three 2 ml (4 mg) CG injections, the first two 15 days apart, and the third one 30 days after the second Bovine/ < 3 kDa Kilinc (2018) [ 72 ] Turkey Prospective, single-center, open-label study (observational) Grade 2 to 3 K-L grade knee OA patients Promerim (hydrolyzed fish collagen) / No control Oral/720-mg Promerim for the first 15 days after admission, and then 360 mg for the second 15 days Fish/NA Mehra (2019) [ 73 ] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Placebo Oral/2 capsules (1 g) of BCC, 2 times daily 1 capsule = 300 mg hydrolyzed collagen type II + 100 mg CS + 50 mg HA Chicken/∼1.5 − 2.5 kDa Stančík (2012) [ 68 ] Slovakia RCT (double-blind) Knee OA patients Undenatured type I collagen (COL-I) vs. Placebo Oral/1 × 8 mg pure lyophilized collagen type I in capsule Bovine/NA Trč (2011) [ 69 ] Czech Republic RCT (double-blind) Knee OA patients Enzymatic hydrolyzed collagen vs. glucosamine sulphate Oral/10 g, once daily NA/NA Observational studies Azeem (2019) [ 70 ] India Open-label observational study Knee OA patients UC-II (undenatured type II collagen)/no control Oral/daily capsule of 40 g of UC-II Obtained from chicken sternum/NA De Luca (2019) [ 71 ] Italy Retrospective study Knee OA patients An injectable collagen formulation consisting of bovine hydrolyzed type I collagen (ChondroGrid) / No control Intra-articular injection/ Three 2 ml (4 mg) CG injections, the first two 15 days apart, and the third one 30 days after the second Bovine/ < 3 kDa Kilinc (2018) [ 72 ] Turkey Prospective, single-center, open-label study (observational) Grade 2 to 3 K-L grade knee OA patients Promerim (hydrolyzed fish collagen) / No control Oral/720-mg Promerim for the first 15 days after admission, and then 360 mg for the second 15 days Fish/NA Mehra (2019) [ 73 ] …”
Section: Resultsmentioning
confidence: 99%
“…In addition, it also has a very good safety profile NA Trč (2011) [ 69 ] Colatech ® (NA) NA 3 months Colatech ® : 47 GS: 46 Colatech ® has demonstrated to be efficient in improving clinical status in knee OA (KOA) patients, with significant improvement in pain scores, functional joint status and a better quality of life. It demonstrated clinically better efficacy than GS after 2, 4, 8, and 12 weeks of treatment NA Observational studies Azeem (2019) [ 70 ] UC-II ® (NA) NA 120 days 100 This study showed that UC-II, a food ingredient containing type II undenatured collagen, significantly improved knee function in a patient with OA knee joint after 120 days of observation Until we conduct longer tests, it remains an open question whether a slow-acting additive, such as UC-II, can affect the biomechanical condition of the knee with OA sufficient to improve the knee’s ROM (knee flexion range) De Luca (2019) [ 71 ] ChondroGrid (CG), (Bioteck, Arcugnano, Italy) NA 6 months 20 patients Results of the present study (…) indicate (that) CG may be a safe and effective adjuvant in the treatment of symptomatic knee OA by intra-articular injection The overall results are extremely promising and highlight the need for further controlled prospective studies to investigate the full extent of the beneficial effects of CG treatment and whether intra-articular CG injection may be more beneficial than other non-pharmacological treatments already available in the clinical practice Kilinc (2018) [ 72 ] NA (NA) No financial support received 1 month 92 patients The results of this single-center, open-label clinical study demonstrate that Promerim is a viable natural treatment option for treating knee OA NA Mehra (2019) [ 73 ] DUPACT ® (Wockhardt...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are hundreds of food supplements available on the market to treat OA. Among them are the most frequently used active ingredients, such as collagen hydrolysates [ 33 ], Curcuma longa and curcumin extracts [ 34 , 35 ], and Boswellia serrata [ 36 , 37 ], which have demonstrated highly and clinically significant short-term reduction in pain [ 38 ]. Others, such as undenatured type II collagen [ 39 ], avocado and unsaponifiable soy [ 40 ], glucosamine, and chondroitin have shown statistically significant improvements in pain management [ 22 , 41 , 42 ], but their clinical significance has not been clearly identified, because long-term effects on inflammation and matrix regeneration still remain to be demonstrated [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous of food supplements are available without prescription in pharmacies and health food stores to treat OA [ 23 , 33 ]. Among the most frequently used active elements, collagen hydrolysates [ 34 ], Boswellia serrata , Curcuma longa [ 35 ] and curcumin extract [ 36 , 37 ], have demonstrated clinically significant short-term reduction in pain [ 38 ]. Other nutraceuticals, such as glucosamine and chondroitin, avocado and unsaponifiable soy [ 39 ] or undenatured type II collagen [ 40 ], have been shown to significantly relieve discomfort associated with OA [ 41 , 42 , 43 ], but their mechanisms and long-term effects on cartilage regeneration and inflammation are still uncertain [ 38 ].…”
Section: Discussionmentioning
confidence: 99%